DEVELOPMENT OF A MULTICULTURAL-BASED SCHOOL MANAGEMENT (MSBM) TRAINING MODEL TO IMPROVE THE PERFORMANCE OF STATE ELEMENTARY SCHOOL PRINCIPALS IN SUBULUSSALAM CITY, ACEH PROVINCE - Ade Amriani; Aman Simare-mare; Yuniarto Mudjisusatyo (SOSIOEDUKASI, 2026)
The objectives of this study are to: (1) To find a Multicultural-Based School Management Training Model (MSBM) to Improve the Performance of State Elementary School Principals in Subulussalam City, Aceh Province. (2) To test the feasibility of the Multicultural-Based School Management Training Model (MSBM) to Improve the Performance of State Elementary School Principals in Subulussalam City, Aceh Province. (3) To measure the effectiveness of the implementation of the Development of a Multicultural-Based School Management Training Model (MSBM) to Improve the Performance of State Elementary School Principals in Subulussalam City, Aceh Province. This type of research is a development research using the ADDIE model. It was carried out in 82 State Elementary Schools spread across 5 sub-districts of the city of Subulussalam, involving 82 school principals as subjects. The research instruments and model design are first validated by experts and tested on midwives to obtain their feasibility and effectiveness of use. The trial was carried out 2 times, namely a limited trial (20 respondents) and a broad trial (62 respondents). Based on the results of the study, it was found: (1) The MSBM Training Model is the development of a Multicultural-Based School Management model to improve the performance of Principals on multicultural school planning, Multicultural-based curriculum management, Multicultural learning supervision, Teacher professional development, Inclusive facilities and infrastructure management, Transparent and equitable financial management, School partnerships and school-based self-evaluation. multicultural so as to improve the performance of the Principal. (2) The feasibility of the MSBM Training Model to improve the performance of school principals in the city of Subulussalam is very valid and very feasible to use. The results of the feasibility test are obtained through expert validation and user trials. The feasibility of the model was reviewed from expert validation of 88.5% (very feasible) and the feasibility test of the model by users of 91.6% (very feasible). (3) The MSBM Training Model is very effective in improving the performance of school principals in carrying out their duties. The improvement in performance can be seen in the results of the second paired t test and the average N-Gain score. The value of sig. (2 tailed) the two trials were < 0.05 so that Ho was rejected and Ha was accepted, meaning that the application of the MSBM training model had an effect on improving the performance of school principals in the city of Subulussalam. The average N-Gain Score (g) for both tests was 0.74 and 0.75. Because the g>0.7 value is in the high category, it can be concluded that the use of the MSBM Training Model can improve the performance of school principals in the city of Subulussalam.